Understanding the Models of Grammar - Mahaputri, Ratna Andhika (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2013)
This article provides comprehensive explanation about several models of grammar. The first model of grammar which is explained is considered from the functional grammar and associated with the American linguist Noam Chomsky that is Transformational Grammar. This model of grammar is consisted of three components they are phrase structure rule, the lexicon, and transformation. The second model of grammar which is explained in this article is Minimalist Grammar. This article also compares her understanding in two models of grammar they are Transformational Grammar and Minimalist Grammar.